Planning and Implementation of Hybrid Event Case Study: Muslim Fashion Festival (MUFFEST), March 18-28, 2021 in Jakarta - Fetty Nurmala Rossi; I Made Adhi Gunadi; Hasnah Amirah Kirana (Politeknik Pariwisata Makassar, Indonesia, 2022)
This study aims to analyze the planning and implementation of Hybrid Event in Jakarta